Fragmentation And Displacement : Edwin‘s Accented Film Practice - Teo, Miaw Lee (IJERT, 2019)
This article aims to explore the sense of displacement and fragmentation evinced in the short films made in the post-Suharto‘s era by Chinese Indonesian independent filmmaker, Edwin. This emphasizes on the sense of dislocation and alienation arguably relates closely to his experience of growing up as Chinese in Indonesia during the New Order period (1966-1998). Under President Suharto‘s government from 1966 to 1998, Chinese Indonesians were placed in a state of uncertainty. In one sense, they were forced to assimilate to the indigenous culture, however, they were constantly reminded of their difference. This paper argues that Edwin‘s films are deeply informed by his personal biography as a Chinese Indonesian, but that this ethnic background appears indirectly, producing an ‗accented‘ form of filmmaking. Edwin brings his own experiences of hybridity and ‗in-betweenness‘ to bear on his filmmaking practice to produce more complex representations of Indonesian society. His upbringing in the socio-political context of the Suharto era, together with his membership of the archipelago‘s long-standing Chinese diasporic community, has contributed to his development as an ‗accented‘ filmmaker.